Desmosterol in human nonalcoholic steatohepatitis. Issue 3 (29th July 2013) - Simonen, Marko; Männistö, Ville; Leppänen, Joel; Kaminska, Dorota; Kärjä, Vesa; Venesmaa, Sari; Käkelä, Pirjo; Kuusisto, Johanna; Gylling, Helena; Laakso, Markku; Pihlajamäki, Jussi
<x xml:space="preserve">Abstract</x> Dysregulation of the cholesterol synthesis pathway and accumulation of cholesterol in the liver are linked to the pathogenesis of nonalcoholic steatohepatitis (NASH). Therefore, we investigated the association of serum and liver levels of cholesterol precursors with NASH. Liver histology was assessed in 110 obese patients (Kuopio Obesity Surgery Study [KOBS] study, age 43.7 ± 8.1 years [mean ± standard deviation, SD], body mass index [BMI] 45.0 ± 6.1 kg/m2). Serum and liver levels of cholesterol precursors were measured with gas‐liquid chromatography. The association between cholesterol precursors and serum alanine aminotransferase (ALT), as a marker of liver disease, was also investigated in a population cohort of 717 men (Metabolic Syndrome in Men Study [METSIM] study, age 57.6 ± 5.8 years, BMI 27.1 ± 4.0 kg/m2). Serum desmosterol levels and the desmosterol‐to‐cholesterol ratio were higher in individuals with NASH, but not in individuals with simple steatosis, compared to obese subjects with normal liver histology (P = 0.002 and P = 0.003, respectively). Levels of serum and liver desmosterol correlated strongly (r = 0.667, P = 1 × 10−9), suggesting a shared regulation. Both serum and liver desmosterol levels correlated positively with steatosis and inflammation in the liver (P < 0.05). Serum desmosterol had a higher correlation with the accumulation of cholesterol in the liver than serum cholesterol. Serum desmosterol levels (P = 2 × 10−6) and the serum desmosterol‐to‐cholesterol ratio (P = 5 × 10−5) were associated with serum ALT in the population study. Conclusion: Levels of desmosterol in serum and the liver were associated with NASH. These results suggest that serum desmosterol is a marker of disturbed cholesterol metabolism in the liver. Whether desmosterol has a more specific role in the pathophysiology of NASH compared to other cholesterol precursors needs to be investigated. (Hepatology 2013;53:976–982)